RFID based security system for vehicle - Norzikri, Sairi (2010)
Lacking of security in the car lead the higher number of reported stolen car. By using RFID as additional security might be reduce the number of stolen vehicle. The system will act as second key to vehicle when the owner wants to start or turn on their vehicle. The objective of this system is to act as additional passive safety for the vehicle. The main components of the system are PIC, RFID reader and tag. All of the components will be assembled according to the design. Then, the PIC will be programmed suit to the application which is to make the PIC send a high signal to the LED. This LED will be modified to the relay to make it possible to the real world application. When the tag is place on the reader, the reader will read and send the data to PIC. The PIC will analyze the data which the serial number of that card and then compare with the number at the PIC itself If the ID is correct, the user can start their car but if the wrong ID, they cannot start the engine. The result shows that the LED is on when the correct tag is put on the RFID reader. As conclusion, this system can be proposed in the automotive industry as a one solution of vehicle theft.